High-Fidelity Anthropometric Facial Measurements Can Be Obtained From a Single Stereophotograph From the Vectra H1 3-Dimensional Camera. (October 2019) - Jodeh, Diana S.; Rottgers, S. Alex
Background: Anthropometry is a well-established means of measuring facial morphology. Although reliable, direct anthropometry can be time-consuming and not conducive to a busy clinical practice. The Vectra H1 handheld stereophotogrammetric system requires 3 stereophotographs taken from different perspectives to generate a three-dimensional (3D) surface. The time needed to take the 3 stereophotographs can increase the possibility of involuntary movements, precluding its use to assess young patients. To overcome this limitation, we evaluated if accurate linear facial measurements can be obtained from a single stereophotograph and compare these to the measurements taken by direct anthropometry. Methods: Twenty pediatric patients, aged 0 to 10 years, who were undergoing minor surgical procedures at Johns Hopkins All Children's Hospital were recruited. Fourteen linear facial distances were obtained from each participant using direct anthropometry under general anesthesia. These same distances were measured using Mirror 3D analysis. Intraclass correlation was used to determine intrarater reliability on duplicate 3D images. Results: Correlation coefficients between 3D imaging in frontal view and direct anthropometric measurements were excellent for 13 measures taken, ranging from 0.8 (subnasale to columella and subnasale to stomion superius) to 0.98 (nasion to subnasale and subnasale to labiale superius). Correlation coefficients between submental view and direct anthropometric measurements were excellent for 13 measures as well, ranging from 0.77 (subnasale to columella) to 0.98 (nasion to subnasale). Conclusions: Linear anthropometric measurements taken from 3D surfaces generated from a single stereophotograph correlate closely with direct anthropometric measures. This improves workflow and applicability of anthropometric studies to our youngest patients.